A new monitoring method for overlying strata failure height in Neogene laterite caused by underground coal mining. (November 2020) - Liu, Shiliang; Dai, Song; Li, Wenping; Han, Bo; He, Ben; Luo, Jinping
Highlights: A new monitoring method for overlying strata failure height in Neogene laterite caused by underground coal mining is presented, solving the inapplicability of traditional monitoring method in clay layer. The monitoring method applicability based on FMI is verified by numerical simulation, and the shapes of water flowing fractured zone in laterite and bedrock are arch-shaped, not saddle-shaped. The evolution mode of WFFZ in laterite layer and bedrock is different, and Neogene laterite layer has inhibitory effect on the WFFZH. Abstract: Determination of the overlying strata failure height, that is, water flowing fractured zone height (WFFZH), is critical to underwater coal mining, especially in the fragile geo-environment areas. Due to the property discrepancy of rock and soil, WFFZH penetrating the clay layer in the Jurassic coalfield cannot be accurately determined by conventional measurement method, a new formation micro-scanner image (FMI) method was presented and verified in the paper. Taking the N1208 coalface in the Shennan mining area, Shaanxi, China, as a case study, FMI based field test for monitoring WFFZH was carried out firstly. The scanning results show that subtle changes of drilling sidewall cracks could be presented intuitively in FMI scanning image, and the WFFZH was be determined as 145.15 m. Secondly, the whole evolutionary process of WFFZH is simulated using UDEC, whose maximum height of WFFZ is calculated as 147.0 m. Comparison results between on-site measurement and numerical simulation suggest that FMI technology is applicable to monitor the WFFZH in laterite layer. Thirdly, in order to illustrate the discrepancies in WFFZH developed in laterite and bedrock, a comparative numerical simulation tests results show that laterite layer has an inhibitory effect on WFFZH.